2017
DOI: 10.1371/journal.pone.0178230
|View full text |Cite
|
Sign up to set email alerts
|

Association between aqueous humor and vitreous fluid levels of Th17 cell-related cytokines in patients with proliferative diabetic retinopathy

Abstract: Inflammation is known to be involved in the progression of diabetic retinopathy. We have recently reported that vitreous levels of IL-4, IL-17A, IL-22, IL-31, and TNFα are higher than the respective serum levels in proliferative diabetic retinopathy (PDR) patients, and that vitreous levels of these cytokines are higher in PDR than in other non-inflammatory vitreoretinal diseases or uveitis associated with sarcoidosis. In the present study, we investigated inflammatory cytokines including Th17 cell-related cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 41 publications
2
32
0
2
Order By: Relevance
“…Binding of SOCS1-KIR to the adaptor protein MAL dysregulates signaling from MyD88 and NF-kB. It is worth noting here that genetic deletion of either MyD88 or NF-kB leads to a resistance to autoimmune disorder (Mc Guire et al, 2013;van Loo et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Binding of SOCS1-KIR to the adaptor protein MAL dysregulates signaling from MyD88 and NF-kB. It is worth noting here that genetic deletion of either MyD88 or NF-kB leads to a resistance to autoimmune disorder (Mc Guire et al, 2013;van Loo et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…Suppression of STAT1 and STAT3 leads to downregulation of the effects of the inflammatory cytokines IL-6 and IL-22 (a cytokine produced by Th17 cells), both of which are elevated in uveitis and related autoimmune disorders (Kim et al, 2016;Sainz-de-la-Maza et al, 2016). Uveitis patients were shown to have elevated levels of IL-22 (Takeuchi et al, 2017). Since IL-22 utilizes JAK2 and TYK2 for its signaling, the effect of this cytokine is likely to be dampened in the presence of R9-SOCS1-KIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study from the same research group further showed that the level of vitreous IL-17A was related significantly to IL-10, IL-22, and TNF-α levels in both vitreous and aqueous humor (Takeuchi et al 2017). One explanation is that the immune response of PDR involves both posterior and the anterior segments (Takeuchi et al 2017). Further investigation is needed to illustrate the IL-17 receptor distribution, the regulation of IL-17-related signaling pathway, and the relevant cytokines or mediators in the different segments of eyes in PDR.…”
Section: Diabetic Retinopathymentioning
confidence: 90%
“…It was found that the level of IL-17A (IL-17) level in the vitreous fluid was correlated significantly with the vitreous levels of cytokines including IL-4, IL-22, IL-31, and TNF-α. A subsequent study from the same research group further showed that the level of vitreous IL-17A was related significantly to IL-10, IL-22, and TNF-α levels in both vitreous and aqueous humor (Takeuchi et al 2017). One explanation is that the immune response of PDR involves both posterior and the anterior segments (Takeuchi et al 2017).…”
Section: Diabetic Retinopathymentioning
confidence: 96%